Reliability of a Skin Diagnostic Device in Assessing Hydration and Erythema. (October 2017) - Huimin, Koh; Rowledge, Alexandra M.; Borzdynski, Caroline J.; Miller, Charne; Frescos, Nicoletta; McKenzie, Gayle; Perry, Elizabeth; McGuiness, William
ABSTRACT: OBJECTIVE: To examine the reliability of a skin diagnostic device, the SD202 (Courage+Khazaka GmBH, Cologne, Germany), in assessing hydration and erythema of periwound skin and pressure injury-prone areas. DESIGN: Intrarater reliabilities from 3 cross-sectional and prospective studies are reported. SETTING AND PARTICIPANTS: Patients attending an outpatient, nurse-led wound dressing clinic (n = 16), a podiatrist-led high-risk foot clinic (n = 17), and residents (n = 38) at a single residential aged-care facility. MAIN OUTCOME MEASURE: Skin hydration and erythema levels assessed using the SD202. MAIN RESULTS: High internal consistency was maintained for consecutive skin hydration and erythema measures at a single point on the venous leg ulcer periwound (α > .996 and α > .970 for hydration and erythema, respectively) and for the pressure-prone areas of the sacrum (α > .916), right (α > .994) and left (α > .967) ischium, right (α > .989) and left (α > .916) trochanter, right (α > .985) and left (α > .992) calcaneus, and right (α > .991) and left (α > .990) lateral malleolus. High consistency was also found for the measures obtained at 4 different locations around the periwound for the venous leg ulcer (α > .935 and α > .870 for hydration and erythema, respectively). In diabetic foot ulcer assessment, acceptable internal consistency of hydration measures around the periwound was observed (α > .634). Internal consistency of erythema measures was variable, ranging from low to high reliability, particularly among predebridement measures. CONCLUSIONS: Using the protocols outlined in this study, the SD202 demonstrates high reliability for assessing skin hydration and erythema levels. It is possible that the SD202 can be used in clinical practice as an appropriate tool for skin hydration and erythema assessment.